Agricultural pesticides and land use intensification in high, middle and low income countries - Schreinemachers P. (2014)
We study levels and trends in agricultural pesticide use for a large cross-section of countries using FAO data for the period 1990-2009. Our analysis shows that a 1% increase in crop output per hectare is associated with a 1.8% increase in pesticide use per hectare but that the growth in intensity of pesticide use levels off as countries reach a higher level of economic development. However, very few high income countries have managed to significantly reduce the level of intensity of their pesticide use, because decreases in insecticide use at higher income levels are largely offset by increases in herbicide and fungicide use. The results also show very rapid growth in the intensity of pesticide use for several middle income countries such as Brazil, Mexico, Uruguay, Cameroon, Malaysia and Thailand. Complementing our analysis with data from the Rotterdam Convention on Prior Informed Consent (PIC), we show that hazardous pesticides covered in the PIC procedure are more weakly regulated in lower than in higher income countries. We discuss the policy challenges facing developing countries with a rapid growth in pesticide use and recommend a four-pronged strategy, including an environmental tax on pesticides with revenues allocated to long-term investments in awareness building, the development of integrated crop management methods and the setting of food safety standards. The interactions between these measures should help contribute to the effectiveness of the overall strategy package. ? 2012 Elsevier Ltd.